2019
DOI: 10.1016/j.jjcc.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan in heart failure with reduced ejection fraction patients: Real world experience on advanced chronic kidney disease, hypotension, and dose escalation

Abstract: Background: Angiotensin receptor and neprilysin inhibition (ARNI) has been shown to reduce cardiovascular mortality by 20% as compared with enalapril in a randomized controlled trial. However, there is a paucity of real-world data on the effects of ARNI in heart failure patients with reduced ejection fraction (HFrEF), especially those with concurrent renal impairment or hypotension. Methods: Between 2016 and 2017, we recruited 466 HFrEF patients treated with sacubitril/valsartan (Group A) and 466 patients mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 27 publications
1
91
0
2
Order By: Relevance
“…28,24 In clinical practice, patients with all stages of kidney disease who receive treatment with sacubitril-valsartan have fewer cardiovascular deaths or hospitalizations for HF than those treated with standard therapy. 23 According to the pooled analysis of serum potassium concentrations greater than 5.5 mmol/L, there was no significant difference between the groups (OR 0.93, P = 0.10), although these concentrations were found in 13.2% of the sacubitril-valsartan group and 15.3% of the valsartan group (P = 0.048) in the PARAGON-HF study. 13 However, regarding the rate of serious hyperkalaemia (≥6.0 mmol/L), sacubitril-valsartan was associated with a lower rate than enalapril or valsartan (OR 0.75, P = 0.0007) in the PARAGON-HF, 13 PARAMOUNT, 9 and PARADIGM-HF studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…28,24 In clinical practice, patients with all stages of kidney disease who receive treatment with sacubitril-valsartan have fewer cardiovascular deaths or hospitalizations for HF than those treated with standard therapy. 23 According to the pooled analysis of serum potassium concentrations greater than 5.5 mmol/L, there was no significant difference between the groups (OR 0.93, P = 0.10), although these concentrations were found in 13.2% of the sacubitril-valsartan group and 15.3% of the valsartan group (P = 0.048) in the PARAGON-HF study. 13 However, regarding the rate of serious hyperkalaemia (≥6.0 mmol/L), sacubitril-valsartan was associated with a lower rate than enalapril or valsartan (OR 0.75, P = 0.0007) in the PARAGON-HF, 13 PARAMOUNT, 9 and PARADIGM-HF studies.…”
Section: Discussionmentioning
confidence: 84%
“…The TRANSITION study 22 showed that the early initiation of sacubitril‐valsartan was selected for patients with acute decompensated heart failure with a reduced ejection fraction either in the hospital or shortly after discharge. A real‐world study involving 932 HFrEF patients verified the effectiveness of sacubitril‐valsartan 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, impressive benefi ts of combining NEP inhibition and angiotensin II type 1 receptor (AT1R) blockade have been demonstrated in the heart failure with a reduced ejection fraction (HFrEF) (7), what markedly turned the clinical attention to NEP. Though a slower clinical acceptation (8), real-world data also confi rmed the effectiveness and safety of NEP inhibitor containing pharmacotherapy (9,10), supporting that NEP plays an important role in the pathophysiology of HFrEF and accentuating NEP as an attractive biotarget in clinical research of HF. It is assumed that NEP levels and/or activity are elevated in settings of HF and, consequently, its inhibition slows the degradation of NPs, enhancing diuresis, natriuresis, myocardial relaxation and anti-remodelling, thus providing clinical benefi t (3,11).…”
Section: Introductionmentioning
confidence: 94%